Identification of Changing Ribosome Protein Compositions using Mass Spectrometry. Issue 20 (23rd October 2018) - Samir, Parimal; Browne, Christopher M.; Rahul; Sun, Ming; Shen, Bingxin; Li, Wen; Frank, Joachim; Link, Andrew J.
Abstract: The regulatory role of the ribosome in gene expression has come into sharper focus. It has been proposed that ribosomes are dynamic complexes capable of changing their protein composition in response to environmental stimuli. MS is applied to identify quantitative changes in the protein composition of S. cerevisiae 80S ribosomes in response to different environmental stimuli. Using quantitative MS, it is found that the paralog yeast ribosomal proteins RPL8A (eL8A) and RPL8B (eL8B) change their relative proportions in the 80S ribosome when yeast is switched from growth in glucose to glycerol. By using yeast genetics and polysome profiling, it is shown that yeast ribosomes containing either RPL8A or RPL8B are not functionally interchangeable. The quantitative proteomic data support the hypothesis that ribosomes are dynamic complexes that alter their composition and functional activity in response to changes in growth or environmental conditions.